2021
DOI: 10.3390/bios11030061
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Optic Sensors: A Review for Glucose Measurement

Abstract: Diabetes mellitus is a chronic metabolic disorder, being globally one of the most deadly diseases. This disease requires continually monitoring of the body’s glucose levels. There are different types of sensors for measuring glucose, most of them invasive to the patient. Fiber optic sensors have been proven to have advantages compared to conventional sensors and they have great potential for various applications, especially in the biomedical area. Compared to other sensors, they are smaller, easy to handle, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 111 publications
(138 reference statements)
0
20
0
Order By: Relevance
“…Examples of BOFS for pH and oxygen detection can be found in Section 3.2.1 and Section 3.2.2 , respectively, whereas those for cancer detection and diagnosis are presented in Section 3.2.3 . In addition, the detection of other diverse biochemical parameters has been recently reported and will be detailed in Section 3.2.4 [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Advances In Optical-fibre-based Biomedical Photonic Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of BOFS for pH and oxygen detection can be found in Section 3.2.1 and Section 3.2.2 , respectively, whereas those for cancer detection and diagnosis are presented in Section 3.2.3 . In addition, the detection of other diverse biochemical parameters has been recently reported and will be detailed in Section 3.2.4 [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Advances In Optical-fibre-based Biomedical Photonic Sensorsmentioning
confidence: 99%
“…Recently, a plasmonic tilted FBG grating sensor (see [94]) based on a p-mercaptophenylboronic acid monolayer and Au nanoparticles for highly sensitive and stable glucose detection was reported [65]. Blood glucose concentration in an average person ranges from 80 to 120 mg/dL (4.4 to 6.6 mM) [66]. In this work, a concentration of glucose in the Other new developments have been carried out towards cost-effective solutions and miniaturization of the sensing systems [93].…”
Section: Other Biochemical Parametersmentioning
confidence: 99%
“…They have all failed to run for an extended period. 4 , 7 , 15 The indirect nature of the measurement and the unavoidable calibration procedure are the most significant hurdles in developing non-invasive glucose measurement sensors. They also necessitate improving the signal-to-noise ratio and sensitivity, evaluating analytical performance, developing accurate blood glucose measurement methodologies, and reducing measurement time.…”
Section: Introductionmentioning
confidence: 99%
“…This paper proposes a new non-invasive blood glucose testing technology that generates and analyzes primary speckle patterns formed by light rays interacting with the skin inside an uncovered multimode optic fiber. Our multimode fiber (MMF)-based optic sensor is developed for non-invasive glucose monitoring systems and can be used to obtain higher sensitivity 15 , 17 19 The experiments involve the subjects’ finger placed on a fiber under normal conditions and under the influence of a magnetic field while the tested subject had varying blood glucose levels. It was found that the magnetic field improves the sensitivity and accuracy of the blood glucose concentration measurements by an uncovered multimode optic fiber sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Among all fiber-optic sensors, tilted fiber Bragg grating (TFBG), in which the refractive index modulation planes are angled by a few degrees relative to the propagation axis, has attracted great attention because it can measure small changes in the surrounding refractive index near the surface of the fiber while simultaneously measuring the temperature for calibrating the temperature-induced cross-sensitivity [3][4][5]. Moreover, TFBG is usually inscribed into the fiber core by using phase-mask or femtosecond laser techniques, which will not introduce any breaks in the structure of the fiber, making it more stable compared to other fiber sensors, such as D-shaped [6,7] and tapered fiber sensors [8][9][10]. Furthermore, owing to the tilt grating-induced break in the cylindrical symmetry of the fiber, some of the power propagating in the core of the fiber can be coupled to the fiber cladding, exciting hundreds of cladding modes traveling backward in the cladding [11].…”
Section: Introductionmentioning
confidence: 99%